Efficacy of Chemical Insecticides and Neem Oil Against White Fly (Bemisia tabaci Genn.) Infesting ladysfinger (Abelmoschus esculentus L.) - Ghosh, S. K.; Mandal, T.; Chakraborty, K. (International Journal of Bio-resource and Stress Management, 2023)
Okra (Abelmoschus esculentus L.) is susceptible to various pests of which white fly (Bemisia tabaci Genn.) causes heavy damage. The field study evaluated the efficacy of nine new insecticides including one phytopesticide neem oil (Azadiracta indica) against this pest during the post-kharif season of 2004 and 2005. Significant differences were found in the efficacy of different treatments in reducing white fly populations. All the insecticides gave a satisfactory control, recording more than 60% mortality. λ-cyhalothrin (Karatzeon) was found most effective insecticide closely followed by a mixed formulation of chloropyriphos and cypermethrin (Nurelle). A rapid degradation of persistency was observed in imidachloprid closely followed by neem oil than other insecticides tested. Satisfactory control (>60% population suppression) was achieved with imidacloprid and neem oil. Imidachloprid, having lower persistency is suitable for white fly control. Neem oil of biological origin (bio-pesticides) have less or no hazardous effects on human health and the environment, therefore, it can be incorporated in IPM programmes and organic farming in vegetable cultivation.